2005
DOI: 10.1111/j.1365-2036.2006.02725.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of single‐dose naproxen on eicosanoid formation in human gastroduodenal mucosa

Abstract: SUMMARY BackgroundIn animal studies, aspirin and non-aspirin non-steroidal anti-inflammatory drugs contribute to gastroduodenal damage via cyclo-oxygenase inhibition and consecutive leucotriene formation (COX-LOX eicosanoid shunt).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
(72 reference statements)
2
1
0
1
Order By: Relevance
“…This study has also shown that SLE patients who had received pulse methylprednisolone therapy and developed gastric mucosal damage had a significantly higher rate of NSAID/ aspirin use, lower gastric TXB2 and lower gastric PGE2 than those without gastric mucosa damage. This study also showed that patients who took NSAIDs/aspirin had significantly lower serum TXB2, lower serum PGE2, lower gastric TXB2, and lower gastric PGE2, which is consistent with other studies [18,22].Taken together, these observations suggest that lower gastric TXB2 and lower gastric PGE2 in these SLE patients with gastric mucosal injury may be due to NSAID/ aspirin effects rather than the methylprednisolone effect. This suggestion was supported by logistic regression analysis showing that NSAID/aspirin usage was the only risk factor for gastric mucosal injury in those SLE patients who had received pulse therapy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study has also shown that SLE patients who had received pulse methylprednisolone therapy and developed gastric mucosal damage had a significantly higher rate of NSAID/ aspirin use, lower gastric TXB2 and lower gastric PGE2 than those without gastric mucosa damage. This study also showed that patients who took NSAIDs/aspirin had significantly lower serum TXB2, lower serum PGE2, lower gastric TXB2, and lower gastric PGE2, which is consistent with other studies [18,22].Taken together, these observations suggest that lower gastric TXB2 and lower gastric PGE2 in these SLE patients with gastric mucosal injury may be due to NSAID/ aspirin effects rather than the methylprednisolone effect. This suggestion was supported by logistic regression analysis showing that NSAID/aspirin usage was the only risk factor for gastric mucosal injury in those SLE patients who had received pulse therapy.…”
Section: Discussionsupporting
confidence: 91%
“…These findings support that pulse methylprednisolone therapy does not inhibit COX-1 function of serum and gastric mucosa and does not cause gastric mucosal injury, although it decreases serum COX-2 activity, which is consistent with previous findings that inhibition of both COX-1 and COX-2 function is required for rat gastric mucosa injury [10]. Although the intra-and interassay variability of ELISA for PGE2 and TXB2 is reportedly high [18,22], Wilcoxon signed rank test was used in this inquiry to compare individual eicosonoids in the same patients before and after pulse therapy. In addition, all the eicosonoids were prepared and measured simultaneously to decrease intraand interassay variability.…”
Section: Discussionsupporting
confidence: 91%
“…One example of a drug that has this activity in horses is carprofen, which when given at the clinically recommended dosage of 0.7 mg/kg IV is a weak inhibitor of COX, but has some inhibitory action of 5‐LOX . There has been some concern that COX‐inhibiting NSAIDs may shunt arachidonic acid toward the LOX enzyme system, thereby enhancing inflammation, but this has not been consistently shown to be the case . Nonetheless, dual inhibitors of both COX and LOX remain a possibility for the future.…”
Section: Renal Effectsmentioning
confidence: 99%
“…Nachdem beide Cyclooxygenasen, COX-1 und COX-2, durch NSAR gehemmt werden, kommt es zu einer vermehrten Bildung von Leukotrienen über die 5-Lipooxygenase (5-LOX). Auch Leukotriene schädigen durch eine toxische Wirkung sowohl Gefäße in der Schleimhaut als auch die Schleimhautbarriere selbst [10,11].…”
Section: Nichtsteroidale Antirheumatika Und Acetylsalicylsäureunclassified